Russian Notarial System Institute in Far East at the End of XIX - the Beginning of ХХ Century - A. V. Druzyaka (Научный диалог)
On the basis of various sources the article considers the historical conditions and peculiarities of formation and functioning of the in the Far East and northeast China, in Harbin. The research urgency is caused by necessity of understanding the role of notaries in the system of social institutions, the general laws and peculiarities of its development in the Far East. The brief description of formation of the system of notary bodies in Russia, the main features of the process of institutionalization of notaries in the region is given. The main legal and institutional conditions of its functioning in different historical conditions are analyzed. The process of formation and activities of notaries in the unique socio-legal and administrative realities of Harbin is considered. The peculiarities of formation of bodies of notaries are covered. Specific examples illuminated the legal and social status of notaries. Special attention is given to processes of institutional transformation of the system of notaries in different historical conditions, including the period of fundamental socio-political and socio-economic changes of 1918-1923. The conclusion is made about the reasons of the high demand for notaries from all segments of the population of the region and its institutional sustainability, manifested in the analyzed period.